Infertile Couple and Pregnancy Outcomes for Patients Undergoing a Pregnancy Program in the Rural Area of Nagekeo District, Flores, East Nusa Tenggara : Pasangan Infertil dan Luaran Kehamilan pada Pasien yang Menjalani Program Kehamilan di Kabupaten Nagekeo, Flores, Nusa Tenggara Timur - Chatarina L. S. D. Dando; Angga Dominius; Jacob T. Salean (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To elucidate the characteristics of infertile couples residing in the rural area of Nagekeo Regency and assess the outcomes of their participation in the local pregnancy program. Methods: We conducted a descriptive study at Aeramo Regional General Hospital (RGH) in Nagekeo Regency, Flores, East Nusa Tenggara (ENT), utilizing a total sampling technique from January 2020 to April 2022. A total of 56 couples participated in this study. Results: The analysis revealed that infertile couples at Aeramo RGH were typically aged between 23 and 35 years, with an average infertility duration exceeding 4 years. Primary infertility was the predominant condition (89.3%), with 55.4% of male partners exhibiting obesity. A significant number of male participants reported alcohol and cigarette consumption. Data were insufficient to determine the prevalence of infertility in men versus women. Notably, the outcomes of the pregnancy program in this region did not demonstrate significant improvements. Conclusions: This study identified potential risk factors such as smoking, alcohol consumption, and obesity that may contribute to infertility; however, it did not establish a strong correlation between these factors and infertility. Moreover, the pregnancy program's outcomes were inconclusive, likely due to limited diagnostic and treatment resources in the area. Keyword: infertility characteristics, pregnancy program, pregnancy outcomes. Abstrak Tujuan : Mendeskripsikan karakteristik pasangan infertil di Kabupaten Nagekeo serta mengetahui hasil luaran kehamilan bagi pasangan yang mengikuti program kehamilan di daerah tersebut. Metode : Penelitian ini merupakan penelitian deskriptif yang dilakukan di Rumah Sakit Umum Daerah (RSUD) Aeramo, Kabupaten Nagekeo, Flores, Nusa Tenggara Timur. Dengan menggunakan teknik total sampling pada periode Januari 2020 - April 2022, terdapat 56 pasangan yang bergabung dalam penelitian ini. Hasil : Hasil penelitian kemudian dianalisis secara univariat dan didapatkan usia pasangan infertil di Aeramo RGH adalah antara 23 - 35 tahun dengan durasi infertilitas lebih dari 4 tahun. Infertilitas primer dan obesitas pada pria mendominasi masing-masing kelompok yaitu 89,3% dan 55,4%. Mayoritas pria mengonsumsi alkohol dan rokok. Tidak ditemukan data yang cukup untuk menentukan apakah infertilitas terjadi pada pria atau wanita. Hasil dari program kehamilan yang dilakukan di daerah ini belum menunjukkan hasil yang signifikan. Kesimpulan : Karakteristik yang memicu faktor risiko seperti merokok, mengkonsumsi alkohol dan obesitas. Meskipun pada penelitian ini belum didapatkan korelasi yang kuat dari faktor risiko tersebut pada infertilitas. Hasil dari program kehamilan belum menunjukkan hasil yang signifikan karena modalitas diagnostik dan pengobatan yang sangat terbatas. Kata kunci : karakteristik infertilitas, luaran kehamilan, program hamil.